Assessment of the socio-economic factors affecting implementation of community-based tsetse control in Busia, Kenya - Kamara, D.; Echessah, P.; Swallow, B.M.; Curry, J. (1995)
The use of baited traps and targets to control the tsetse fly has the potential for successful and sustainable trypanosomiasis control by local communities. However, with community-based programmes, community organisational capacity, incentives needed to initiate and sustain programmes, and intra-community distribution programmes become important issues. A multi-disciplinary study in a sleeping sickness foci in Busia district, Kenya in investigating this and other issues, using participatory, focus group and formal survey methods. Findings to date indicate the existence of a complex set of linkages between human health and animal trypanosomiasis and human health, subsistence and nutrition, resulting in multiple social and biological impacts on local populations. Various factors including ownership and use of livestock, beliefs and attitudes concerning trypanosomiasis, and the length and degree of exposure to the disease and control programmes appear to be important determinants of the willingness of both the communities and individuals to participate in control activities.